Identification and fungicide screening of Phyllosticta capitalensis causing leaf spot on sweet viburnum in China - Wen LI; Yixuan RUAN; Zhengping BIAN; Yueqiu HE; Kai FENG; Liang LIU; Zhilong WANG; Feng HUANG (Phytopathologia Mediterranea)
Sweet viburnum (Viburnum odoratissimum Ker-Gawl.) is a widely used ornamental plant, which has dense branches and leaves, and fast spreading and evergreen habit. In October 2022, leaf spot symptoms were observed in a hedge of sweet viburnum in Yuanshi Garden, Ningbo, China. Fungi were isolated from symptomatic leaves, and were identified using morphological characteristics and phylogenetic analyses of partial sequences of internal transcribed spacer (ITS), actin (act), and translation elongation factor 1-alpha (tef1-α), and were evaluated in pathogenicity tests. The causal agent of sweet viburnum leaf spot was identified to be Phyllosticta capitalensis. Effects of seven fungicides on P. capitalensis were assessed in vitro. Fungicide EC50s (mg L-1) against P. capitalensis were: 270.77 for 75% chlorothalonil (WP); 0.02 for 250 g L-1 azoxystrobin SC; 0.27 for 10% difenconazole WDG; 0.02 for 75% trifloxystrobin + tebuconazole WDG, 9.03 for 35% fluopyram + tebuconazole SC, 5.90 for 500 g L-1 fluazinam SC, and 89.11 for 10% prothioconazole SC. Among these, azoxystrobin SC and trifloxystrobin + tebuconazole WDG could be used for control of viburnum leaf spot. This is the first report of P. capitalensis causing leaf spot of sweet viburnum, and this study provides guidance for chemical management sweet viburnum leaf spot, and on other host plants.